Sex differences in the association between atherogenic index of plasma and α-klotho: insights from a community-based cohort - Xiaoyan Tang; Jie Liu; Hongwei Li; Zili Chen; Li Yang; Rui Du (Annals of Medicine)
Background The Atherogenic Index of Plasma (AIP) is a marker of lipid imbalance and cardiovascular risk, while α-Klotho is an anti-aging protein involved in oxidative stress and inflammation regulation. Although both are linked to cardiovascular and metabolic health, the relationship between AIP and α-Klotho, particularly regarding sex differences, remains unclear.Methods We performed a cross-sectional analysis of a community-based cohort drawn from five consecutive cycles of the NHANES (January 2007 – December 2016). A total of 4,897 participants aged 40 to 79 years were included. Weighted multivariate linear regression models assessed the association between AIP and serum α-Klotho (SαKl) levels, adjusting for demographic and clinical covariates. Sex-stratified analyses explored potential effect modification.Results Mean ± SE SαKl level was 869.9 ± 8.6 pg/mL in females and 826.6 ± 10.2 pg/mL in males; mean ± SE AIP values were −0.09 ± 0.01 and 0.05 ± 0.01, respectively. In the fully adjusted model, participants in the third (Q3) and fourth (Q4) AIP quartiles had significantly lower SαKl than those in Q1 (Q3: β = −40.32; 95% CI: −75.89, −4.75; p = 0.031, Q4: β = −41.03; 95% CI: −80.27, −1.78; p = 0.046). Sex-stratified analysis showed a stronger inverse association in females (Q3: β = −73.13; 95% CI: −123.58, −22.69; p = 0.006, Q4: β = −99.79; 95% CI: −154.68, −44.89; p < 0.001), whereas no significant relationship was observed in male.Conclusion AIP is inversely associated with SαKl in this community-based cohort, particularly among females, suggesting dyslipidemia may contribute to lower SαKl levels in a sex-specific manner. AIP could help identify individuals—especially females—at risk of SαKl deficiency. Prospective studies are warranted to confirm causality and to determine whether improving lipid profiles can preserve SαKl and related health outcomes.